Tingkat Kesiapan Kali Pepe untuk Dikembangakan sebagai Kawasan Wisata Berbasis Sungai di Kota Surakarta - Nurul Widowati; Winny Astuti; Murtanti Jani Rahayu (Universitas Sebelas Maret Surakarta, 2017)
Surakarta is a city that has the potential of the river. But in the process, these rivers suffered environmental degradation as a function instead of the banks into slums and squatter, and functions of rivers that serve as places of waste disposal. Government’s city of Surakarta has done various setup area of the river. One of the targeted structuring Pepe-River is often known by the name Kali Pepe. Kali Pepe is the river which has the most strategic location because it divides the centre of city and the river has a past history of Surakarta. Kali Pepe is the witness of history where culture and trade activities in the rapidly growing city of Surakarta in the past with the ecological function and physical function as transportation trade.Setuping Kali Pepe, according to the Mayor of Surakarta, is directed to serve as recreation/tourism area. Since the Surakarta Mayor initiated the year 2015 that Kali Pepe as a tourist area. The initiated moves the government and society in order to more actively participate in developing the area into a tourist area. This research would like to know how the readiness level of the Kali Pepe area to be developed as a tourist area-based streams. The components of preparedness were seen from aspect of attractions or natural tourist attraction, artificial attractions, acessesiblity, institutional, infrastructure supporting tourism, and the behavior of the flooding of the river. This research is quantitative research in methods of scoring analysis. The result of this research has shown that Kali Pepe less readiness to be developed as a tourist area-based stream. Aspects of accessibility and infrastructure supporting tourism were an aspect which has a readiness. But for this aspect of the attraction, institutional and river flooding behavior is still in the stage of less readiness. Keywords: readiness, tourist areas, river tours